Analysis of service quality and customer satisfaction at the Sky Lounge And Cafe padang state university hotel padang - Reynaldy Reynaldy; Kasmita Kasmita; Wiwik Gusnita; Rahmi Holinesti (Universitas Negeri Padang, 2025)
Sky Lounge and Café at UNP Hotel Padang is a culinary service business unit with a modern concept and exclusive services. Maintaining and improving service quality remains a strategic challenge, as it directly impacts customer satisfaction and loyalty. This study analyzes consumer perceptions of service quality and its effect on satisfaction using a quantitative approach, with 100 respondents selected through accidental sampling. The results show that all service quality dimensions (tangibles, reliability, responsiveness, assurance, empathy) were rated in the